Respon Siswa Menggunakan Media Pembelajaran Daring Berbasis Aplikasi WhatsApp pada Pembelajaran IPA di Masa Pandemi Covid-19 - Suci Pratiwi; Ika Nurani Dewi; Safnowandi Safnowandi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2021)
This study aims to determine student responses using online learning media based on WhatsApp applications in science learning during the covid-19 pandemic. This is a survey research by using quantitative and qualitative methods. The sample used is class V SD Negeri 1 Labuapi for the academic year 2020/2021 as many as 20 students. The instruments used are interview sheets and student response questionnaire sheets. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions or verification. The results of the study based on the research objectives, namely student attention in online learning based on WhatsApp applications from the results of the questionnaire 75% strongly agree, 48.75% Relevance, 55% Confidence, 39.28% Satisfied. Based on the objectives and results of the research, it can be concluded that students' attention in online learning based on WhatsApp applications obtained 75% questionnaire results in the positive category, 48.75% in the non-positive category, 55% confidence in the less positive category, and 39.28% satisfaction in the non-positive category.